2013
DOI: 10.1016/j.rser.2013.02.032
|View full text |Cite
|
Sign up to set email alerts
|

The essence of future smart houses: From embedding ICT to adapting to sustainability principles

Abstract: a b s t r a c tIn the context of intelligent environments, the smart houses are often pointed as one of the main constituents of smarter living environments. This study attempts to theoretically analyze case models of smart houses in order to identify their essence and characteristics. The results show that the most significant intelligent values embodied in smart houses embrace technologies of the functional automation. In fact, smart houses are substantially intertwined with integrated ICT technologies which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 42 publications
0
55
0
10
Order By: Relevance
“…It can be programmed according to the needs of one or more users, ensuring comfort and convenience [25]. Even though technology has a higher added value, many are designed to generate a saving of resources over time [26]. Maintenance in such cases depends on each article.…”
Section: Discussionmentioning
confidence: 99%
“…It can be programmed according to the needs of one or more users, ensuring comfort and convenience [25]. Even though technology has a higher added value, many are designed to generate a saving of resources over time [26]. Maintenance in such cases depends on each article.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the design technological innovation can be facilitated by means of effective sustainability assessment, which in turn achieve low carbon building development. It is not unusual that ICT is used to monitor the energy consumption, water consumption and carbon emissions of buildings [53,54].…”
Section: Development Of Low-carbon Theories and Technologiesmentioning
confidence: 99%
“…Context-awareness is technology that can recognize human activities, voices and the environmental changes surrounding people [2], and it makes it possible to identify their wishes and to control the environment to provide necessary services to the occupants. Much further study is needed on the collection of data, including on activities of daily living, for context-awareness research in living spaces, to do this the end various research is progressing in actual living spaces equipped with devices, and in which users have wearable sensors [3].…”
Section: Introductionmentioning
confidence: 99%